Development of Commercial Equipment Store Management System - YUVARANI; Mohmad Hassim, Yana Mazwin (Applied Information Technology And Computer Science, 2023)
Online system is very useful to manage all the business activities in this fast-moving world. The main purpose of this study to identify and improve the manual-based system of GNS commercial equipment store. The problems of using the existing system were collected and analyzed through interview and questionnaire. The existing considered not much convenient as all the business processes done manually by the staffs which consumes time and tedious work. Therefore, the proposed management system allows the store to run their business activities every day through online. It is expected that the system will help the store owner and staffs to manage and monitor their business tasks in their store efficiently.